Assessment of dental photography imaging as a diagnostic tool for incipient pits and fissures caries in permanent posterior teeth - Omer, Husein Al; Firdous, Rayyan A. Al; Shamrani, Salma Hamed Al; Anazi, Saqer Suwayyid Al; Natto, Zuhair S.; Dayel, Omer Al (Edelweiss Applied Science and Technology, 2025)
Concurrently, dentistry has embraced technological advancements, incorporating digital imaging techniques in various applications [1]. This crossover study aimed to assess digital dental photography imaging as a diagnostic tool for detecting incipient pits and fissure carious lesions in permanent teeth and its correlations with traditional visual examination according to ICDAS II. Direct intraoral clinical examinations were conducted by two AEGD residents and two calibrated restorative consultants trained in the ICDAS II grading system. A total of 34 occlusal surfaces of premolars and molars were examined. Only healthy teeth, enamel hypomineralization, and non-cavitated carious surfaces were included. Non-carious hard tissue defects, fissure sealants, and direct and indirect restorations were excluded. The digital photographs were obtained by two examiners and then blindly assessed in a presentation room using a large screen. The actual scoring of pit and fissure carious lesions in 18 extracted premolar teeth was examined under a clinical microscope based on the downer histological examination. Sensitivity and positive predictive value were highest in photographic examination compared with visual in three observers, while specificity and negative predictive value were equal between visual and photographic examination. From the survey, we compared differences in caries and non-caries detection between PAADI Instructors and PAADI Residents using the Mann-Whitney U test. Residents are more likely to overestimate the results compared with the instructors (P value < 0.05). The Az values for the different examination methods compared with the gold standard (histologic examination) were calculated. The Az values of the two examiners (Consultant 2 and Resident 1) were highest for the visual examination, while it was highest for the photographic examination for Consultant 1 and Resident 2. Visual clinical examination should be the standard for detecting incipient occlusal pit and fissure carious lesions, and digital photographic imaging is a valid diagnostic tool as well.